2016
DOI: 10.1038/srep36134
|View full text |Cite
|
Sign up to set email alerts
|

RSK1 protects P-glycoprotein/ABCB1 against ubiquitin–proteasomal degradation by downregulating the ubiquitin-conjugating enzyme E2 R1

Abstract: P-glycoprotein (P-gp) is a critical determinant of multidrug resistance in cancer. We previously reported that MAPK inhibition downregulates P-gp expression and that P-gp undergoes ubiquitin–proteasomal degradation regulated by UBE2R1 and SCFFbx15. Here, we investigated the crosstalk between MAPK inhibition and the ubiquitin–proteasomal degradation of P-gp. Proteasome inhibitors or knockdown of FBXO15 and/or UBE2R1 cancelled MEK inhibitor-induced P-gp downregulation. RSK1 phosphorylated Thr162 on UBE2R1 but di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 39 publications
0
25
2
Order By: Relevance
“…This may be because RSKs are known to have unidentified, as well as overlapping functions (31). Furthermore, a previous study demonstrated that RSK1 increases ABCB1 expression by suppressing its ubiquitination and proteasomal degradation in human cancer cells (20), which is not consistent with our results. Discrepancies with the previous study might be due to the functional differences of RSKs between mice and humans.…”
Section: Discussioncontrasting
confidence: 99%
“…This may be because RSKs are known to have unidentified, as well as overlapping functions (31). Furthermore, a previous study demonstrated that RSK1 increases ABCB1 expression by suppressing its ubiquitination and proteasomal degradation in human cancer cells (20), which is not consistent with our results. Discrepancies with the previous study might be due to the functional differences of RSKs between mice and humans.…”
Section: Discussioncontrasting
confidence: 99%
“…Although it is less likely that p90RSK is mediating resistance through increased drug efflux given our results in Fig. S2, it could still be possible that p90RSK1 induced upregulation of P-glycoprotein may contribute to the observed resistance via drug efflux as recently describe by Katayama et al (34). These findings not only secure its role in mediating ganetespib resistance in KRAS mutant NSCLC, but also identify p90RSK as a central targetable node to prevent or overcome resistance.…”
Section: Discussionmentioning
confidence: 52%
“…In this current manuscript, we have not identified the key p90RSK substrate(s) that are responsible for inducing resistance to ganetespib; however, we are actively pursuing these targets. p90RSK family has been implicated in the regulation of cell growth and protein synthesis, cell migration and survival, cell proliferation, and cell-cycle progression and in some cases drug efflux (24,33,34). Although it is less likely that p90RSK is mediating resistance through increased drug efflux given our results in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The role of p38 in cell survival is well documented, and evidence suggests that inhibiting Akt allows p38 to promote cell survival (45,46), which may be the case in our study as we show that BX795 blocks Akt activity. RSK1 also regulates cell survival (47) and down-regulates the ubiquitin-conjugating enzyme E2 R1 (48). ICP0, encoded in the HSV-1 genome, is an E3 ubiquitin ligase that requires the E2 enzyme to perform various roles in HSV-1 infection including the efficient establishment of infection (49).…”
Section: Discussionmentioning
confidence: 99%